Tsunami Disaster Preparedness Among School Community: New Evidence From Emerging Country - Haryani; Ezra Aditia; Friska Seftiyani; Rini Asmariati; Listy Vermana (Sumatra Journal of Disaster, Geography and Geography Education, 2026)
This study evaluates the tsunami preparedness levels of six schools in Nagari Kataping, Padang Pariaman Regency, West Sumatra—one of the world's most vulnerable regions. A quantitative survey was conducted involving 160 respondents, including students, teachers, and principals. Preparedness was assessed based on five parameters: knowledge and attitudes, policies and guidelines, emergency response plans, early warning systems, and resource mobilization. Non-parametric tests (Kruskal–Wallis and Mann–Whitney U) were used to analyze significant variations in preparedness among the schools, with overall scores ranging from